Light nuclei femtoscopy and baryon interactions in 3 GeV Au+Au collisions at RHIC - Aboona, Bassam; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physics letters, 2025)
We report the measurements of proton-deuteron (p-d) and deuteron-deuteron (d-d) correlation functions in Au+Au collisions at sNN = 3 GeV using fixed-target mode with the STAR experiment at the Relativistic Heavy-Ion Collider (RHIC). For the first time, the source size (RG), scattering length (f0), and effective range (d0) are extracted from the measured correlation functions with a simultaneous fit. The spin-averaged f0 for p-d and d-d interactions are determined to be -5.28 ± 0.11(stat.) ± 0.82(syst.) fm and -2.62 ± 0.02(stat.) ± 0.24(syst.) fm, respectively. The measured p-d interaction is consistent with theoretical calculations and low-energy scattering experiment results, demonstrating the feasibility of extracting interaction parameters using the femtoscopy technique. The reasonable agreement between the experimental data and the calculations from the transport model indicates that deuteron production in these collisions is primarily governed by nucleon coalescence.
Online verfügbar: 28. März 2025, Artikelversion: 1. April 2025
*The STAR Collaboration: B. E. Aboona, I.M. Deppner, N. Herrmann, Y.H. Leung, Y. Söhngen [und 361 weitere Personen]
Gesehen am 25.09.2025